"Peroperative estimation of bone quality and primary dental implant stability". (April 2019) - Voumard, Benjamin; Maquer, Ghislain; Heuberger, Peter; Zysset, Philippe K.; Wolfram, Uwe
Abstract: Objectives: Dental implants are widely used to restore function and appearance. It may be essential to choose the appropriate drilling protocol and implant design in order to optimise primary stability. This could be achieved based on an assessment of the implantation site with respect to bone quality and objective biomechanical descriptors such as stiffness and strength of the bone-implant system. The aim of this ex vivo study is to relate these descriptors with bone quality, with a pre-implantation indicator of implant stability: pilot-hole drilling force (Fdrilling ), and with two post-implantation indicators: maximal implantation torque (Timplantation ) and resonance frequency analysis (RFA). Methods: Eighty trabecular bone specimens were cored from human vertebrae and bovine tibiae. Bone volume fraction (BV/TV), a representative for bone quality, was obtained through micro-computed tomography scans. Implants were kept in controlled laboratory conditions following standard surgical procedures. Forces and torques were recorded and RFA was assessed after implantation. Off-axis compression tests were conducted on the implants until failure. Implant stability was identified by stiffness and ultimate force (Fultimate ). The relationships between BV/TV, Stiffness, Fultimate and Fdrilling, Timplantation, RFA were established. Results: Fdrilling correlated well with BV/TV of the implantation site (r 2 = 0.81), stiffness (r 2 = 0.75) and Fultimate (r 2 = 0.80). Timplantation correlated better with stiffness (r 2 = 0.86) and Fultimate (r 2 = 0.94) than RFA (r 2 = 0.77 and r 2 = 0.74, respectively). Conclusion: Our results indicate that BV/TV and bone-implant stability can be directly estimated by the force needed for the pilot drilling that occurs during the site preparation before implantation. Moreover, implantation torque outperforms RFA for evaluating the mechanical competence of the bone-implant system. Graphical abstract: Trabecular bone samples were embedded and microCT scanned to evaluate the bone volume fraction, a bone quality substitute. Starting with the implantation procedure, a pilot hole was drilled and the axial force measured. Dental implants were inserted and the torque recorded. A resonance frequency analysis was performed directly after implantation. A mechanical test until failure was conducted to determine the stiffness and strength of the bone-implant system. All the metrics of primary stability were compared to each other and with stiffness and ultimate force (red arrows). fx1 Highlights: Evaluation of the pilot drilling force﻿ as a measurement of implant﻿ primary stability. Bone volume fraction can be estimated by the ﻿force measured during pilot drilling.